Peningkatan pengetahuan dan keterampilan kesehatan gigi melalui pendekatan preventif pada masyarakat Desa Lamlumpu Lhok, Peukan Bada Aceh Besar - Zahara, Elfi; Keumala, Cut Ratna; Andriani, Andriani; Liana, Intan (Jurnal PADE: Pengabdian & Edukasi, 2025)
Oral and dental health is a very important aspect of overall health that should not be ignored by everyone. The importance of increasing public awareness of oral and dental health based on government targets is very necessary to support Healthy Indonesia in 2030. The purpose of this community service is to increase public knowledge by conducting dental health education and practicing skills by brushing teeth together. Behavior in terms of oral and dental health is an aspect that must be considered because a person's behavior is very dependent on the knowledge they have. This community service uses lecture and interview methods. The target of this community service activity is the community of Lamlumpu Lhok Peukan Bada Aceh Besar Village, totaling 30 people. Before the education, a pre-test was conducted, then interviews were conducted with the community to measure their level of knowledge. The realization of this activity can increase community knowledge and abilities about dental health. The results of this community service activity show an increase in community knowledge about oral and dental health from 56,7% pretest to 83% posttest and DMF-T results with the number of respondents 10 people with moderate criteria (1-3). Based on the results of this activity, it can be concluded that there was an increase in public knowledge after being given counseling in the form of lectures and an increase in the correct way of brushing teeth.